1985
DOI: 10.1111/j.1600-0765.1985.tb00442.x
|View full text |Cite
|
Sign up to set email alerts
|

On the physicochemistry of plaque calcification and the phase composition of dental calculus

Abstract: The main constituents of human dental calculus are a carbonate containing apatite and a Mg and Zn containing Whitlockite. A third important component is octocalcium phosphate. If the salivary pH is low enough, human dental calculus can also contain dicalcium phosphate dihydrate. According to the physicochemical model of calculus formation, dental calculus must contain calcite as the main component in animals having a high salivary pH. This hypothesis appeared to be valid for a salivary pH of 8 or higher (dogs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…1). A key determinant of calculus formation may be a small pH rise, because of either loss of carbon dioxide, a natural buffer from saliva, or bacterial metabolic activity [40,41]. A corollary to this is the observation in animals that a high sugar diet, which would have led to a lowering of plaque pH (see below), resulted in low calculus and high caries [42].…”
Section: Calculus Composition and Formationmentioning
confidence: 99%
“…1). A key determinant of calculus formation may be a small pH rise, because of either loss of carbon dioxide, a natural buffer from saliva, or bacterial metabolic activity [40,41]. A corollary to this is the observation in animals that a high sugar diet, which would have led to a lowering of plaque pH (see below), resulted in low calculus and high caries [42].…”
Section: Calculus Composition and Formationmentioning
confidence: 99%
“…For this reason, the distinctive form of endogenous salivary and gingival crevicular fluid of each species, such as pH, glycoprotein, ion content and saliva flow rate, is the primary determinant of colonization of bacterial species, due to the fact that the primary nutrients of oral microbiota are saliva and gingival crevicular fluid [34] . The salivary pH of dogs (pH=8) and cats (pH=7.5) is quite different [35] , presumably leading to distinctive calculus microbiota. In the formation of calculus, basic condition, calcium, inorganic phosphate, alkaline phosphatase and protease are the relevant factors which stimulate calculus origin [36] , and these factors may vary across various species leading to altered oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Boyle et al (1994) showed the value of p53 in saliva as a marker for squamous cell carcinoma, detected and identified tumor-specific mutations in p53 in preoperative salivary samples of individuals suffering from head and neck squamous cell carcinoma. Also, salivary kallikrein were observed in patients diagnosed with malignant tumors as compared with those individuals diagnosed with benign tumors and salivary CA 125 assay who had a better diagnostic value than the comparable serum assay 5,16,17 . …”
Section: Saliva and Cancermentioning
confidence: 98%
“…Proline rich proteins, IgA, lactoferrin, lysozyme and amylase may bind specifically to plaque bacteria and act as receptors for attachment. Composition levels similar to salivary pellicle can be monitored to reach the periodontal disease diagnosis 5,6 .…”
Section: Diagnosis Of Periodontal Diseasesmentioning
confidence: 99%